Pengaruh Pemberian Kombinasi Kompres Jahe Merah dan Air Rebusan Serai terhadap Tingkat Nyeri Penderita Gout Arthritis - Nesih Fitriah; Dewi Siti Oktavianti; Aprizal Ponda (Poltekkes Kemenkes Padang, 2024)
Gout arthritis is a disease characterized by bouts of severe pain in the joint area with high levels of uric acid in the blood. Pain in gout arthritis causes uncomfortable effects and can interfere with daily activities in sufferers. Pain in gout arthritis can be overcome with non-pharmacological therapy, namely red ginger compresses and lemongrass boiled water. The purpose of this study was to determine the effect of giving a combination of red ginger compress and lemongrass boiled water on pain levels in gout arthritis. This research design uses quasy experiment with two group pre and post design. The research location in RW 002 Pisangan Village, Ciputat, South Tangerang in May 2023. The sample size of 32 people was divided into 2 groups: 16 intervention groups and 16 control groups. This research instrument used demographic sheets, observation sheets and Numeric Rating Scale (NRS). The sampling technique in this study uses total sampling. Statistical test using T-test. paired T-test obtained p value = 0.0001 means that there is an effect of giving a combination of red ginger and lemongrass compresses on pain levels. The results of the Independent T-test obtained a P value of 0.0001, meaning that there was a difference in pain levels in the intervention group and the control group after treatment.The results of this study are expected to be one of the non-pharmacological therapies to reduce pain levels in patients with gout arthritis.